The roles of lithium-philic giant nitrogen-doped graphene in protecting micron-sized silicon anode from fading - Liu, Xiaoxu (2015)
A stable Si-based anode with a high initial coulombic efficiency (ICE) for lithium-ion batteries (LIB) is critical for energy storage. In the present paper, a new scalable method is adopted in combination with giant nitrogen-doped graphene and micron-size electrode materials. We first synthesize a new type of freestanding LIB anode composed of micron-sized Si (mSi) particles wrapped by giant nitrogen-doped graphene (mSi@GNG) film. High ICE (>85%) and long cycle life (more than 80 cycles) are obtained. In the mSi@GNG composite, preferential formation of a stable solid electrolyte interphase (SEI) on the surface of graphene sheets is achieved. The formation and components of SEI are identified for the first time by using UV-resonance Raman spectroscopy and Raman mapping, which will revive the study of formation and evolution of SEI by Raman. New mechanism is proposed that the giant graphene sheets protect the mSi particles from over-lithiation and fracture. Such a simple and scalable method may also be applied to other anode systems to boost their energy and power densities for LIB.